Antipulverization Electrode Based on Low‐Carbon Triple‐Shelled Superstructures for Lithium‐Ion Batteries. Issue 34 (21st June 2017) - Zu, Lianhai; Su, Qingmei; Zhu, Feng; Chen, Bingjie; Lu, Huanhuan; Peng, Chengxin; He, Ting; Du, Gaohui; He, Pengfei; Chen, Kai; Yang, Shihe; Yang, Jinhu; et al.
Abstract : The realization of antipulverization electrode structures, especially using low‐carbon‐content anode materials, is crucial for developing high‐energy and long‐life lithium‐ion batteries (LIBs); however, this technology remains challenging. This study shows that SnO2 triple‐shelled hollow superstructures (TSHSs) with a low carbon content (4.83%) constructed by layer‐by‐layer assembly of various nanostructure units can withstand a huge volume expansion of ≈231.8% and deliver a high reversible capacity of 1099 mAh g −1 even after 1450 cycles. These values represent the best comprehensive performance in SnO2 ‐based anodes to date. Mechanics simulations and in situ transmission electron microscopy suggest that the TSHSs enable a self‐synergistic structure‐preservation behavior upon lithiation/delithiation, protecting the superstructures from collapse and guaranteeing the electrode structural integrity during long‐term cycling. Specifically, the outer shells during lithiation processes are fully lithiated, preventing the overlithiation and the collapse of the inner shells; in turn, in delithiation processes, the underlithiated inner shells work as robust cores to support the huge volume contraction of the outer shells; meanwhile, the middle shells with abundant pores offer sufficient space to accommodate the volume change from the outer shell during both lithiation and delithiation. This study opens a new avenue in the development of high‐performance LIBs for practical energy applications. Abstract : SnO2 triple‐shelled hollow superstructures with a low carbon content (4.83%) can withstand a huge volume expansion of ≈231.8% and deliver a high reversible capacity of 1099 mA h g −1 even after 1450 cycles, due to their self‐synergistic structure‐preservation behavior that protects the superstructures from collapse and guarantees the electrode structural integrity during long‐term cycling.